6(7+2p)=3(p

Simple and best practice solution for 6(7+2p)=3(p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(7+2p)=3(p equation:



6(7+2p)=3(p
We move all terms to the left:
6(7+2p)-(3(p)=0
We add all the numbers together, and all the variables
6(2p+7)-(3p=0
We multiply parentheses
12p-(3p+42=0

See similar equations:

| -7.8d=-1.56 | | 400+25x=68+25x | | 9x+22=-15 | | -9w+1=7-7w | | ⅓(m+21)+⅔m=-2 | | 4+4=-4(5x-2) | | 1,500+25h+3=3,000 | | (X-11)/11=11(11x-121) | | 2(x+3=-12 | | 1,500-25h=3,000 | | (x+1.4)+1.4x=(x+0.2)+5.96 | | 1,500+25h=3,000 | | 3x^2+6x=81 | | 2=2/7x-6 | | (3*6/2)v+10=3v*3v+9 | | x+3.2−5.4=4.8 | | 170.00+.25m=320.00 | | $170.00+$0.25m=$320.00 | | 0.25(16x-8)+1/5(10x-15)=-29 | | -.1x=2 | | -11+35=-4(x+9) | | d−(−12)=100 | | -5(7x+5)=-35x+25 | | 3(4x+9)=-46+37 | | 4x=38-2x-8 | | 5+3=7+2q | | 7^5x+4=63 | | -11+35=4(x+9) | | 2=w/4 | | r-(-14)=17 | | 7(x+2)=x*5 | | 200+10n=100+30n |

Equations solver categories